Classic and advanced ceramics : from fundamentals to applications - Heimann, R. B. (Robert Bertram), 1938- (Weinheim : Wiley-VCH, 2010)
Based on the author's lectures to graduate students of geosciences, physics, chemistry and materials science, this didactic handbook covers basic aspects of ceramics such as composition and structure as well as such advanced topics as achieving specific functionalities by choosing the right materials. The focus lies on the thermal transformation processes of natural raw materials to arrive at traditional structural ceramics and on the general physical principles of advanced functional ceramics. The book thus provides practice-oriented information to readers in research, development and enginee.
Introduction to classic ceramics -- Mineralogy, structure, and green processing of clay minerals -- Important ceramic phase systems -- Mineralogy and chemistry of the ceramic firing process -- Mineralogy and chemistry of cements -- Introduction to advanced ceramics -- Oxide ceramics: structure, technology, and applications -- Electroceramic materials -- Superconducting ceramics -- Bioceramic materials -- Non-oxide ceramics: structure, technology, and applications -- Advanced ceramic processing and future development trends -- Construction of the phase diagram of a binary system A-B with an ideal solid solution -- Thermodynamics of displacive phase transitions -- Radial electron density distribution (RED) function -- Thermodynamics of spinodal decomposition of crystals -- Theory of superconductivity.
Includes bibliographical references and index.
Print version record.
Keywords: Ceramics; Ceramic materials; Ceramic materials; Ceramics; Electronics -- Materials; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Ceramic materials; Ceramics; Electronic books